Dehumanization through humour and conspiracies in online hate towards Chinese people during the COVID‐19 pandemic. (2nd May 2022) - Sakki, Inari; Castrén, Laura
Abstract: Since the beginning of the COVID‐19 pandemic, there have been widespread conversations about the origins of the virus and who to blame for it. This article focuses on the online hate directed at Chinese and Asian people during the pandemic. Taking a critical discursive psychological approach, we analysed seven online threads related to COVID‐19 and China from two Finnish websites (Suomi24 and Ylilauta) and one US (8kun) site. We identified three discursive trends associated with dehumanising Chinese populations: 'monstrous Chinese', 'immoral Chinese' and 'China as a threat', which created different forms of dehumanisation on a continuum from harsher dehumanisation to milder depersonalisation. The animalistic metaphors, coarse language, humorous frames and conspiracy beliefs worked to rhetorically justify the dehumanisation of Chinese individuals, making it more acceptable to portray them as a homogeneous and inhumane mass of people that deserves to be attacked. This study contributes to the field of discursive research on dehumanisation by deepening our knowledge of the specific features of Sinophobic hate speech.